2017
DOI: 10.3390/plants6040045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Polyphenol Contents and Antioxidant Activities between Ethanol Extracts of Vitex negundo and Vitex trifolia L. Leaves by Different Methods

Abstract: The in vitro antioxidant potential assay between ethanolic extracts of two species from the genus Vitex (Vitex negundo L. and Vitex trifolia L.) belonging to the Lamiaceae family were evaluated. The antioxidant properties of different extracts prepared from both plant species were evaluated by different methods. DPPH scavenging, nitric oxide scavenging, and β-carotene-linoleic acid and ferrous ion chelation methods were applied. The antioxidant activities of these two species were compared to standard antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
4
30
1
1
Order By: Relevance
“…To our knowledge, there are little or no available data in the literature about the TPC and TFC of the selected plants; thus, only a few papers could be found related to the TPC and TFC of other species of the same families. The leaf extract of Vitex negundo has recently been reported to contain 89.71 mg GAE/g of TPC and 63.11 mg QE/g of TFC [30], which are relatively higher values than our study. Shahat et al [31] reported TPC in the range from 11 to 56 mg GAE/g of DW for different species of Asteraceae family, which is a lower value than our findings.…”
Section: Resultscontrasting
confidence: 66%
“…To our knowledge, there are little or no available data in the literature about the TPC and TFC of the selected plants; thus, only a few papers could be found related to the TPC and TFC of other species of the same families. The leaf extract of Vitex negundo has recently been reported to contain 89.71 mg GAE/g of TPC and 63.11 mg QE/g of TFC [30], which are relatively higher values than our study. Shahat et al [31] reported TPC in the range from 11 to 56 mg GAE/g of DW for different species of Asteraceae family, which is a lower value than our findings.…”
Section: Resultscontrasting
confidence: 66%
“…Closely related plant species have been shown to have similar phytochemical constituents ( Diris et al, 2017 ). The antioxidant activities of V. pinnata ’s close relatives, V. agnus-cactus , V. negundo and V. trifolia have also been determined using various solvents, and was found that the fruits and leaves of these Vitex plants were significantly capable of scavenging free radicals ( Rashed, 2013 ; Saklani et al, 2017 ), signifying that Vitex plants are potential sources of promising antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic content was high in the ethanol extract than the aqueous extract, and this property is attributed to their antioxidant activity. This is mainly due to the ability of the extracts to absorb and neutralize the free radicals, to quench the singlet, or triplet oxygen species [28]. The total flavonoid content was also found to be high in ethanol extract than the aqueous extract.…”
Section: Deeksha and Arunachalammentioning
confidence: 95%